Governing by numbers: audit culture, rankings and the new world order. (February 2015) - Shore, Cris; Wright, Susan
<x xml:space="preserve">Abstract</x> Quantification and statistics have long served as instruments of governance and state power. However, in recent decades new systems of measurement and rankings have emerged that operate both beyond and below the nation‐state. Using contemporary examples, we explore how international measurements, rankings, risk management and audit are creating new forms of global governmentality. We ask, who – or what – is driving the spread of audit technologies and why have indicators and rankings become a populist project? How should we theorise the rise of measuring, ranking and auditing and their political effects? What are the impacts of these ever‐more pervasive systems on organisational behaviour and professional life?